Dynamics of Surfactant Clustering at Interfaces and Its Influence on the Interfacial Tension: Atomistic Simulation of a Sodium Hexadecane-Benzene Sulfonate-Tetradecane-Water System (2018)
The process of equilibration of the tetradecane-water interface in the presence of sodium hexadecane-benzene sulfonate is studied using intensive atomistic molecular dynamics simulations. Starting as an initial point with all of the surfactants at the interface, it is obtained that the equilibration time of the interface (several microseconds) is orders of magnitude higher than previously reported simulated times. There is strong evidence that this slow equilibration process is due to the aggregation of surfactants molecules on the interface. To determine this fact, temporal evolution of interfacial tension and interfacial formation energy are studied and their temporal variations are correlated with cluster formation. To study cluster evolution, the mean cluster size and the probability that a molecule of surfactant chosen at random is free are obtained as a function of time. Cluster size distribution is estimated, and it is observed that some of the molecules remain free, whereas the rest agglomerate. Additionally, the temporal evolution of the interfacial thickness and the structure of the surfactant molecules on the interface are studied. It is observed how this structure depends on whether the molecules agglomerate or not.